Evaluating a Novel Hydrocolloid Alternative for Yogurt Production: Rheological, Microstructural, and Sensory Properties - F. N. U. Akshit; Ting Mao; Shwetha Poojary; Venkata Chelikani; Maneesha S. Mohan (Foods, 2025)
This study aimed to assess the viability of a new gelling agent, formed by a combination of disodium 5-guanylate and lactic acid, as a potential substitute for conventional hydrocolloids in yogurt production. Six different yogurt samples containing novel gel (combination of lactic acid and disodium 5-guanylate), disodium 5-guanylate, gelatin, agar-agar, lactic acid, and a control yogurt without any hydrocolloid or other additives, were studied. As expected, all the yogurt samples exhibited shear-thinning behavior. The novel gel yogurt, when compared to the control yogurt, displayed similar viscosity at a low shear rate of 4.5 s−1 (mimicking the shearing during manual scooping with a spoon) and lower viscosity at a shear rate of 60.8 s−1 (mimicking the agitation in the mouth). Notably, the novel gel yogurt demonstrated a lower flow behavior index (0.13 vs. 0.40 on day 1), reduced syneresis (23.37% vs. 33.75%), and had a higher consistency coefficient (9.2 vs. 7.25 on day 1) compared to the control yogurt. The novel gel yogurt exhibited superior rupture strength compared to yogurt with other hydrocolloids, such as gelatin and agar-agar, and similar brittleness to yogurt with gelatin. Microstructural analysis revealed an aggregated and compact protein network in the novel gel yogurt, analogous to the yogurt with gelatin. Sensory evaluations indicated no significant differences between the control and the novel gel yogurt. Therefore, the novel gelling agent studied can serve as a cost-effective alternative in yogurt production, compared to conventional hydrocolloids that are in short supply, in high demand, and expensive in the market.